2016
DOI: 10.1039/c6cc04984b
|View full text |Cite
|
Sign up to set email alerts
|

A fast response and red emission probe for mammalian thioredoxin reductase

Abstract: The first red emission off-on probe, TRFS-red, for thioredoxin reductase was reported. Compared to the previous green emission probe TRFS-green, TRFS-red maintains a high selectivity to the redox enzyme yet with improved response rate and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…The probe showed a 56-fold selectivity for TrxR (50 nM) over the GSH (1 mM). Based on the previous published data 11,13 , the selectivity of TRFS-green and TRFS-red for TrxR over GSH were calculated to be 15.6 and 12.8, respectively. The crude HeLa cell extracts also showed robust activity in eliciting the fluorescence from Fast-TRFS, and this activity was dose-dependently inhibited by a selective TrxR inhibitor auranofin (AF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probe showed a 56-fold selectivity for TrxR (50 nM) over the GSH (1 mM). Based on the previous published data 11,13 , the selectivity of TRFS-green and TRFS-red for TrxR over GSH were calculated to be 15.6 and 12.8, respectively. The crude HeLa cell extracts also showed robust activity in eliciting the fluorescence from Fast-TRFS, and this activity was dose-dependently inhibited by a selective TrxR inhibitor auranofin (AF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we reported a series fluorescent probes of TrxR, including TRFS-green, TRFS-red and Mito-TRFS (Fig. 1a) 1113 . The practical applications of TRFS probes in multiple types of cells have facilitated the studies of TrxR, which have been demonstrated by not only our group but also researchers from other groups 1421 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such prodrugs are expected to display high efficacy to those TrxR‐overexpressing cancer cells with less side effects on noncancerous cells. In our previous studies, we developed several fluorescent probes for mammalian TrxRs (TrxR fluorogenic substrates, TRFS series). These probes contain a five‐membered cyclic disulfide (1, 2‐dithiolane) scaffold, which can be efficiently reduced by TrxRs in the presence of NADPH but is resistant to other related enzymes and biological thiols.…”
Section: Discussionmentioning
confidence: 99%
“…alkyl 2-imidazolyl disulphides 1–3 8 ( 2 , whose K i value toward the enzyme was determined as 31 µM, is also known as PX-12 and has been in Phase 1 clinical trials for advanced metastatic cancer and was stopped due to safety concerns 6 ), disodium 2,2′-dithio-bis-ethane sulphonate 4 9 (also known as Travocept TM which advanced through phase III clinical trials in patients with non-small cell lung cancer and has a K m value of 72 µM 6 ) as well as bicyclic disulphide-containing natural products chaetocin ( 5 ), gliotoxin ( 6 ) and chaetomin ( 7 ) which have been shown to possess K m values of 4.6 µM, 16.9 µM, and 16.1 µM, respectively – and have demonstrated a substrate-competitive inhibition profile toward TrxR1 and pro-apoptotic efficacy toward cancer cells 10 . Other disulphide compounds – 5,5′-dithiobis(2-nitrobenzoic acid) ( 8 also known as DTNB or Ellman’s reagent) 11 , thioredoxin reductase fluorogenic substrate ( 9 or TRFS-green) 12 and mitochondria-targeted “mito-TRFS” ( 10 ) 13 have not been employed as TrxR inhibitors but rather as fluorescent probes, also due to their being substrate (disulphide-linked Trx) analogues. Based on the structure of these disulphide TrxR ligands, we designed a series of symmetric ( 11 ) and non-symmetric ( 12 – 13 ) derivatives of dithiodiglycolic acid (Figure 1).…”
Section: Introductionmentioning
confidence: 99%